2016
DOI: 10.1016/j.ejr.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution CT and pulmonary function tests in rheumatoid arthritis patients with subclinical interstitial lung disease in Kuwait

Abstract: Background: Interstitial lung disease (ILD) is a frequent extra-articular manifestation of RA and can cause significant morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Findings of HRCT that did not fall under any defined category were labeled as others, as were present in five (9.3%) patients. [18]. The discrepancy in the mean age of the patients in our study may be present due to the small sample size.…”
Section: Hrct -High-resolution Computed Tomographymentioning
confidence: 60%
See 1 more Smart Citation
“…Findings of HRCT that did not fall under any defined category were labeled as others, as were present in five (9.3%) patients. [18]. The discrepancy in the mean age of the patients in our study may be present due to the small sample size.…”
Section: Hrct -High-resolution Computed Tomographymentioning
confidence: 60%
“…Affara NK et al examined HRCT abnormalities in their study, i.e., GGO was present in 30%, air space opacification (AS) was present in 13.3%, mixed AS/GGO was present in 13.3%, honeycombing in 10%, septal thickening in 26.7% and traction bronchiectasis in 11.7% of the subjects [18]. In contrast with these studies, our study reported interlobular septal thickening as the most common HRCT finding, present in 22 (40.7%) patients and illustrated in Similarly, GGO was present in 21 (38.9%) patients (Figure 2), nine (16.7%) patients had honeycombing.…”
Section: Diagnosismentioning
confidence: 99%
“…This study showed that about 3/4 of the studied patients had subclinical ILD identified by HRCT (about 1/4 of them had minimal disease). However, in Nasr et al 17 38.3% (23/60) of all involved RA patients had subclinical ILD and only 16 patients (26.7%) had an abnormal pulmonary function. In addition, in Gochuico et al 6 , 21 33% having RA had subclinical ILD.…”
Section: Discussionmentioning
confidence: 84%